Media Literacy in Montenegro - Perovic, Jelena (2015)
Few countries in the world have introduced media education into their curriculums. Montenegro became one of them in 2009, when “media literacy” was introduced as an optional subject for 16 and 17 year old students of Gymnasium high schools. This article presents the findings of the first and only research conducted so far on media education in Montenegro. It is a national case study which examines the potential of media education to change the school culture and accelerate education system reform towards embracing the new digital education paradigm in the future. The focus is on the results of research conducted through in-depth interviews with media literacy teachers all over the country. Despite the many challenges, all teachers identify the potential of media education to strengthen some of the key competences of the students and to improve their motivation and academic performance. They also identify potential to change positively school culture by transforming teachers into “cultural mediators” (Morcellini, 2007) and by supporting the formation of a “participative culture” (Jenkins & Kelley, 2013) in schools. This research recommends focusing education reform on spreading the media education pedagogy to the entire curriculum in order to embrace the new digital education paradigm in the future.